Pengujian Hadits Ahad Dengan Al-qur’an (Studi Komparatif Syafi’iyyah dan Hanafiyah) - Agusri Fauzan (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
One of the efforts of the scholars in sterilizing the hadith from counterfeiting is to criticize the hadith. Because by criticizing a hadith it will be known whether the hadith is authentic, da'eef, or maudhu '. Criticism of the hadith itself is divided into two, namely criticism of matan and sanad. Historically, criticism of Matan was born earlier than criticism of Sanad. Matan criticism was already in the time of the Prophet Muhammad, while sanad criticism only emerged after the slander among Muslims, namely the division between them following the killing of Usman bin Affan in 35 AH To determine whether or not a hadith was accepted, the hadith scholars have establish the rules of the righteousness. Where all of that has been poured out in detail in the discussions of science must al-hadith. But lately, the jurists who have an interest in using hadith as a source of law, do not stop at the testing set by muhadditsin. They added some more testing criteria so that the hadith was truly believed to be something that was sourced from the Prophet and could be used as proof and practiced. Among these tests is confirming the Prophet's hadith with the Qur'an, sunnah masyhûrah and ‘general al-balwa. In this paper the author will try to explore briefly related to this issue which includes: How are the views of scholars (muhaddits and fuqaha ') regarding the confirmation of the hadith with the above three things, the arguments used by scholars related to their opinions, and their practical examples in in confirming the hadith.